‘Without Water, There is no life’: Urban struggles for water access and processes of citizenship construction in marginalized neighborhoods in Argentina (1970–2000) - Moreno, Lucila (2025)
This article examines the relationship between citizenship and urban infrastructure by focusing on the struggles of residents in marginalized neighborhoods to access water supply networks, within broader conflicts over land appropriation and the right to remain in place. Drawing on a relational and anthropological perspective on citizenship and infrastructure, the study explores how water networks mediate power and domination over time, and how processes of citizenship construction emerge through infrastructure-related disputes involving multiple social, economic, and political actors—beyond the state itself. The analysis is based on long-term anthropological fieldwork, where residents’ struggles for water emerged as central in present-day narratives and memories. Using diverse methodological strategies, including in-depth interviews and the analysis of secondary sources, the article examines water struggles from the 1970s to the 2000s in marginalized neighborhoods of northern Greater Buenos Aires, Argentina. We argue that, in complex and sometimes contradictory ways, residents challenged prevailing expectations, norms, and behaviors imposed on low-income communities and informal settlements without land titles. Through these processes of conflict and negotiation over water access, the boundaries between state, private actors, infrastructure, and citizenship were shaped and redefined from the margins.